Dynamic Susceptibility Contrast Magnetic Resonance Imaging Protocol of the Normal Canine Brain - Stadler, Krystina L.; Pease, Anthony P.; Ballegeer, Elizabeth A. (Frontiers in Veterinary Science, 2017)
ABSTRACT Perfusion MRI, specifically dynamic susceptibility MRI (DSC-MRI) is routinely performed as a supplement to conventional MRI in human medicine for patients with intra-cranial neoplasia and cerebrovascular events. There is minimal data on the use of DSC-MRI in veterinary patients and a DSC-MRI protocol in the veterinary patient has not been described. Sixteen normal dogs, 6 years or older were recruited for this study. The sample population included 11 large dogs (>11kg) and 5 small dogs (<11kg). DSC-MRI was performed on a 1.5T MRI using an adjusted protocol inherent to the MRI. Contrast media was injected using an automatic power injector. Injections were made after 5 MR measurements were obtained. Following image acquisition, an arterial input function (AIF) graph mapping the transit time of contrast within the cerebral arteries was generated. The manually selected time points along this graph were used to compute perfusion maps. A dose and rate of 0.1mmol/kg gadolinium-based contrast media at 3ml/sec followed by 10ml saline flush at 3ml/sec was used in all dogs greater than 11kg. In all dogs >11kg, a useable arterial input function (AIF) and perfusion map was generated. One dog less than 11kg received the same contrast dose and rate. In this patient, the protocol did not generate a useable AIF. The remainder of the dogs less than 11kg followed a protocol of 0.2mmol/kg gadolinium-based contrast media at 1.5ml/sec with a 10ml saline flush at 1.5 ml/sec. A useable AIF and perfusion map was generated in the remaining dogs <11kg using the higher contrast dose and slower rate protocol. This study establishes a contrast dose and administration rate for canine DSC-MRI imaging that is different in dogs greater than 11kg compared to dogs less than 11kg. These protocols may be used for future applications to evaluate hemodynamic disturbances in canine intracranial pathology.